Neuroprotective effects of chloroform and petroleum ether extracts of Nigella sativa seeds in stroke model of rat - Mohammad Akhtar; Aliyu Muhammad Maikiyo; Abul Kalam Najmi; Razia Khanam; Mohd Mujeeb; Mohd Aqil (Wolters Kluwer Medknow Publications, 2013)
Purpose: Stroke still remains a challenge for the researchers and scientists for developing ideal drug. Several new drugs are being evaluated showing excellent results in preclinical studies but when tested in clinical trials, they failed. Many herbal drugs in different indigenous system of medicine claim to have beneficial effects but not extensively evaluated for stroke (cerebral ischemia). Aim: The present study was undertaken to evaluate chloroform and petroleum ether extract of Nigella sativa seeds administered at a dose of 400 mg/kg, per orally for seven days in middle cerebral artery occluded (MCAO) rats for its neuroprotective role in cerebral ischemia. Materials and Methods: Focal cerebral ischemia was induced by middle cerebral artery occlusion for two hours followed by reperfusion for 22 hours. After 24 hours, grip strength, locomotor activity tests were performed in different treatment groups of rats. After completing behavioral tests, animals were sacrificed; brains were removed for the measurement of infarct volume followed by the estimation of markers of oxidative stress. Results: Both chloroform and petroleum ether extracts-pretreated rats showed improvement in locomotor activity and grip strength, reduced infarct volume when compared with MCAO rats. MCA occlusion resulted in the elevation of levels of thiobarbituric acid reactive substance (TBARS), while a reduction in the levels of glutathione (GSH) and antioxidant enzymes viz. superoxide dismutase (SOD) and catalase levels were observed. Pre-treatment of both extracts of Nigella sativa showed reduction in TBARS, elevation in glutathione, SOD, and catalase levels when compared with MCAO rats. Conclusion: The chloroform and petroleum ether extract of Nigella sativa showed the protective effects in cerebral ischemia. The present study confirms the antioxidant, free radical scavenging, and anti-inflammatory properties of Nigella sativa already reported.